PKM Kelompok Taman Kanak-kanak Islam YLPI Riau Perhentian Marpoyan dalam Upaya Peningkatan Kualitas Pendidikan di Kota Pekanbaru - Adni, Dita Fisdian; Abdillah, Satrio (Jurnal Pengabdian UNDIKMA, 2023)
This community service aims to empower the YLPI Riau Islamic Kindergarten Perhentian Marpoyan by providing infrastructure assistance still unavailable in the kindergarten. In addition, counseling was given about personal hygiene and the introduction of traffic rules to kindergarten students. The method used in this service had several stages, starting from the procurement of infrastructure, implementation, and evaluation monitoring. The partner in this service was the YLPI Riau Perhentian Marpoyan Islamic Kindergarten. The instrument for evaluating community service activities was in the form of a questionnaire and is analyzed descriptively. The result was that after the dedication was carried out in the form of providing infrastructure assistance, namely replicas of the Kaaba, replicas of traffic signs, storage cabinets, educational game tools, reading books, and educational posters, as well as computers, activities such as manasic-hajj guide, introduction to orderly traffic rules, activities administration in the administration section as well as other activities carried out in class can finally be carried out smoothly. Apart from that, from counseling about personal hygiene, students understood personal hygiene starting from washing hands, using hand sanitizers, and brushing their teeth. Meanwhile, from the introduction of traffic rules, students at YLPI Perhentian Marpoyan Islamic Kindergarten understood the meaning of traffic signs so they could interpret them on the road and wanted to obey them.